当前位置: X题卡 > 所有题目 > 题目详情

(﹣x)dx等于(  )

查看本题答案

你可能感兴趣的试题

[f(x)+f(x-a)]dx  [f(x)+f(a-x)]dx  [f(x)-f(a-x)]dx  [f(x)-f(x-a)]dx  
g(x)  2xg(x)  xg(x)  2xg(x)  
g(x2)  2xg(x)  x2g(x2)  2xg(x2)  
dx+dy  2dx+2dy  2dx+dy  dx+2dy  
1  2  3  4  
xsinxdx  (x+sinx)dx  xcosxdx  (e+x)dx  
xf′(x)-f′(x)+c  xf′(x)-f(x)+c  xf′(x)+f′(x)+c  xf′(x)+f(x)+c  
-(1/x)+c  1/x+c  -lnx+c  1nx+c  
ʃln2xdx  2ʃln xdx   2ʃln(1+x)dx  ʃln2(1+x)dx  
∫f(x)f’(xdx)  ∫xf2(x2)f’(x2)dx  ∫x2f(x3)f’(x3)dx  ∫3x3f2(x3)f’(x3)dx  
F(sinx)+f  -F(sinx)+c  F(cosx)+c  -F(cosx)+c  
(A) [∫f(x)dx]'=∫f(x)dx=f(x).  (B) ∫d[∫f(x)dx]=f(x).  (C) d[∫f(x)dx]=f(x)dx.  (D) 若∫f(x)dx]'=[∫g(x)dx]',则∫f(x)dx=∫g(x)dx.  
f(x)  f(x)dx  f(x)+C  f’(x)dx  
[f(x)+f(x-]dx  [f(x)+f(a-x)]dx  [f(x)-f(a-x)]dx  [f(x)-f(x-]dx  

热门试题

更多